Stillbirth and Associated Factors Among Women Who Gave Birth at Hiwot Fana Specialized University Hospital, Harar, Eastern Ethiopia - Mengistu, Seble; Debella, Adera; Mulatu, Teshale; Mesfin, Firehiwot; Danusa, Kababa Temesgen; Dheresa, Merga (Frontiers in Pediatrics, 2022)
Background: Stillbirth which accounts for half of all perinatal mortality is not counted on policy, program, and investment agendas around the globe. It has been underestimated public health burden, particularly in developing countries. Ethiopia is among the top countries with a large prevalence of stillbirth in the world. However, there is a dearth of study on the current magnitude of stillbirth in the study area. Therefore, this study intended to assess the prevalence of stillbirth and its associated factors to bridge the gap. Method: A Hospital-based retrospective study was conducted from 01-28 February,2019 and data were collected by reviewing the chart records of all women who gave birth in the past two years (January , 2016, to December , 2018) at Hiwot Fana Specialized University Hospital. Data were entered into Epi data version 4.2.0.0 software and transported to SPSS version 23 for analysis. Descriptive statistics such as frequency, mean and standard deviations were generated. Determinants of stillbirth were analyzed using binary logistic regression and presented by adjusted odds ratio (AOR) with a 95% Confidence Interval (CI). Result: The prevalence of stillbirth was 14.5% (95% CI: 11.7%, 17.6%). Low birth weight (AOR=2.42, 95% CI: 1.23-4.76), prematurity (AOR=2.10, 95% CI: 1.10-4.01), premature rupture of membrane (AOR=2.08, 95% CI: 1.14-3.77), Antepartum hemorrhage (AOR=3.33, 95% CI: 1.66-6.67), obstructed labor (AOR=2.87, 95% CI: 1.48-5.56) and preeclamsia (AOR=2.91, 95% CI: 1.28- 6.62) were an independently associated with stillbirth. Conclusion: The prevalence of stillbirth in this study was high. Low birth weight, preterm birth, premature rupture of the membrane, Antepartum hemorrhage, obstructed labor, and preeclampsia were independently associated with a stillbirth. Therefore, much work is needed involving different stakeholders to reduce stillbirths by improving the health status of women through the provision of quality maternal care including referral systems.